LAKU IN ATTAINING PERFECTION OF LIFE ACCORDING TO JAVANESE MANUSCRIPT “NGELMI PANGRUCAT” - Kunthi Nawaruci; Endang Nurhayati; Hesti Mulyani (Universitas Negeri Makassar, 2021)
Abstract: Laku in Attaining Perfection of Life According to Javanese Manuscript “Ngelmi Pangrucat”. Life tranquility is something which is always wanted by everyone. The last purpose of tranquil life achievement is to reach the perfection of life in this world and hereafter. However, not everyone is aware of behaving well to attain the life tranquility. Regarding to this, the role of ancestors’ writings in the form of Javanese manuscript is very important to deepen human understanding in achieving the perfection of life in which the contents contained remain relevant to be used as life guidance. How is laku? This article explains about manners (laku) to reach life perfection based on Javanese manuscript entitled Ngelmi Pangrucat. This study employed descriptive method by using modern philology theory approach. The result of the study is the text on Ngelmi Pangrucat manuscript with latin characters which are correct. Additionally, sentences were found containing the steps of Ngelmi Pangrucat in the form of laku in order to attain the tranquility and perfection of life on earth and hereafter.